Assessment of Apparent Diffusion Coefficient (ADC) Measurements in Diffusion-Weighted Magnetic Resonance Imaging (DW-MRI) to Distinguish Between Prostate Cancer, Prostatitis, and Normal Prostate - Zehra, Syeda Mariam; Dildar, Nazia; Omar, Saima; Nisar, Uzma; Qayyum, Adil; Awan, Fareeha (Pakistan Armed Forces Medical Journal, 2026)
Objective: To evaluate the diagnostic precision of ADC measurements in distinguishing between prostatitis, normal prostate tissue, and prostate cancer through Diffusion-Weighted Imaging (DWI).Study Design: Comparative Cross-sectional StudyPlace and Duration of Study: Radiology department of the CMH Rawalpindi, Pakistan, from Sep to Dec 2023.Methodology: The study comprised 60 patients with elevated PSA levels of more than 4 ng/ml and a suspicion of prostate cancer. It was decided to use convenience sampling. In order to distinguish between benign prostate tissue, prostatitis, and malignancy, an MRI procedure was put into place. With an ADC cut-off value of 0.92 (x 10-3 mm2/sec), data was collected, entered, and analyzed, and sensitivity and specificity of each cut-off were associated. A one-way ANOVA test was used to compare the ADC values among the groups.Results: The final analysis included the histopathologic examination of TRUS-guided biopsy for 55 patients. The sample's mean age was 59.93 ±8.76. The mean ADC values for normal tissue, prostatitis, and prostate cancer were 1.16 ±.10x10-3 mm2/s, 1.50 ±.07 x 10-3 mm2/s, and 0.85 + 0.1x 10-3 mm2, respectively. The difference was statistically significant (P